Research on the mechanism of drug–drug interaction between salvianolate injection and aspirin based on the metabolic enzyme and PK-PD model: study protocol for a PK-PD trial - Zhang, Wantong (Trials, 2018)
BACKGROUND: Coronary heart disease (CHD) is a common cardiovascular disease accounting for 10–20% mortality by heart disease worldwide. The gold standard treatment to manage CHD is aspirin, which may prevent myocardial infarction and sudden death; however, long-term use of aspirin may increase its side effects. Currently, more and more clinicians are exploring different approaches to use the right combination of medicine to enhance the efficacy and reduce side effects. Salvianolate can significantly inhibit the aggregation and activation of platelets in patients with CHD; however, its optimum combination with western medicine is not established or supported by clinical trial results. METHODS/DESIGN: This trial is a prospectively planned, open-labeled, parallel-grouped, single-centered clinical trial with aggregated pharmacodynamics-pharmacokinetics (PK-PD) data. All treatment courses will last for 10 days and blood sample will be acquired before administration on days 8, 9, and 10, and after administration at 5 min, 15 min, 30 min, 45 min, 1 h, 2 h, 4 h, 8 h, 12 h, and 24 h on day 10. This trial uses PK-PD modeling to provide a description of the concentration–effect relationship and an estimate of pharmacological potency of the medicine. The primary outcome will be changes in aspirin esterase and catechol-o-methyltransferase (COMT) activity at different blood concentrations to determine the PK-PD characteristics of the combination of salvianolate and aspirin, followed by analysis of the correlation between exposure level and pharmacodynamic index of the medicines. DISCUSSION: This trial will aim to evaluate the relationship between changes in the pharmacokinetics and therapeutic effect index in the combined use of salvianolate and aspirin. It also discusses the possible mechanism of medicine combination in the treatment for CHD and provides an experimental basis for a clinically rational medicine combination. TRIAL REGISTRATION: ClinicalTrials.gov, NCT03306550. Registered on 9 October 2017. ClinicalTrials.gov https://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid=S0007D8H&selectaction=Edit&uid=U0003QY8&ts=2&cx=oiuc9g ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13063-018-2861-7) contains supplementary material, which is available to authorized users.